2019
DOI: 10.1016/j.toxrep.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde produced from d-ribose under neutral and alkaline conditions

Abstract: Highlights d -ribose can produce formaldehyde under neutral and alkaline conditions in vitro. Administration of d -ribose induces an increase of formaldehyde in the brain of mice. Formaldehyde in urine and serum should be monitored for a person especially an elderly individual to take d -ribose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…It is therefore proposed that selective inhibition of ribose glycosylation may be used as a therapeutic strategy for the prevention of Alzheimer's disease and type 2 diabetic encephalopathy ( 71 ). Wang et al ( 72 ) also indicated that in alkaline environments, D-ribose may decompose to formaldehyde by the reverse aldol reaction, and that by determining the content of formaldehyde in various parts of mice, it was suggested that formaldehyde produced by D-ribose accumulates in the brain of the mice and that the accumulation of endogenous formaldehyde to pathological concentrations may lead to disturbance of consciousness and cognition. However, it was also hypothesized that accumulation of D-ribose-induced AGEs is an important means underlying the occurrence and development of diabetic encephalopathy ( 62 ).…”
Section: Potential Hazards Of High Concentrations Of D-ribosementioning
confidence: 99%
“…It is therefore proposed that selective inhibition of ribose glycosylation may be used as a therapeutic strategy for the prevention of Alzheimer's disease and type 2 diabetic encephalopathy ( 71 ). Wang et al ( 72 ) also indicated that in alkaline environments, D-ribose may decompose to formaldehyde by the reverse aldol reaction, and that by determining the content of formaldehyde in various parts of mice, it was suggested that formaldehyde produced by D-ribose accumulates in the brain of the mice and that the accumulation of endogenous formaldehyde to pathological concentrations may lead to disturbance of consciousness and cognition. However, it was also hypothesized that accumulation of D-ribose-induced AGEs is an important means underlying the occurrence and development of diabetic encephalopathy ( 62 ).…”
Section: Potential Hazards Of High Concentrations Of D-ribosementioning
confidence: 99%
“…Peraxisomal catalase is capable of oxidizing formaldehyde to fumarate in the presence of hydrogen peroxide. Creation of hydrogen peroxide is the rate limiting step in this reaction, which does not account for a great deal of formaldehyde metabolism [39]. Formaldehyde is considered a hallmark of lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, formaldehyde was regarded as a risk factor for age-related cognitive impairment [46]. Intraperitoneal injection with D-ribose (3.2g/kg bw, once daily) leads to an increase in formaldehyde in the mouse brain [47]. These finding suggest that high dose D-ribose intake induces toxicity.…”
Section: Discussionmentioning
confidence: 99%